Pengaruh Latihan Passing Bawah Dengan Metode Berhadapan Terhadap Peningkatan Teknik Passing Bawah Bola Volly Pada Siswa Ekstrakurikuler Smp Negeri 01 Bermani Ilir - Melan Afriansah; Asnawati Asnawati; Deffri Anggara (Journal Of Dehasen Educational Review, 2026)
The purpose of this study was to determine and analyze the effect of underhand passing training with the facing method on improving the underhand passing technique of extracurricular students of SMP Negeri 01 Bermani Ilir. This study is a study with experimental treatment. The sample in this study was 20 extracurricular students of SMP Negeri 01 Bermani Ilir. Data collection techniques were by means of tests and measurements and observations, data analysis was the significance test "f". The results of the study showed that there was an effect of underhand passing training with the facing method on improving the underhand passing technique of extracurricular students of SMP Negeri 01 Bermani Ilir. There was a difference in the pretest results of 2.356 changing to 2.228 after the posttest had a difference of 0.128 meaning there was an increase of 5.75%. There is a difference between the experimental group of training with the facing method and the control group of underhand passing using a target wall on the underhand passing ability of extracurricular students of SMP Negeri 01 Bermani Ilir in 2025. The results of the comparison of the two training methods concluded that underhand passing training using a target wall was better than underhand passing training with the facing method on the underhand passing ability of extracurricular students of SMP Negeri 01 Bermani Ilir in 2025. There was a difference in the pretest results of 52.90 changing to 49.00 after the posttest had a difference of 3.90 meaning there was an increase of 7.96%.